2012
DOI: 10.1021/jp309469j
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Adsorption of Bulk Self-Assembling Porphyrins at Solid/Liquid Interfaces through the Self-Assembly Process

Abstract: Controlling the adsorption behavior of bulk-phase self-assembling dye molecules at solid/liquid interfaces is of importance for application to various devices. Herein, we report an unexpected phenomenon on the adsorption behaviors of bulk J-aggregating water-soluble porphyrin diacids. A comparative study on the adsorption amounts of J-aggregated meso-tetrakis(4-sulfonatophenyl)porphyrin diacid from freshly prepared and pre-aged solutions revealed enhanced adsorption through the self-assembly process (EASAP). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Porphyrins are promising components that can be employed in various applications due to their desirable structural and functional properties. Moreover, prophyrins are capable of being incorporated into metal–organic–polymer aerogels, which have both the physicochemical properties of porphyrins and the permanent porosity of MOPAs . Porphyrin-based metal–organic frameworks have been extensively investigated , as a versatile synthetic base for porous metal–organic frameworks due to their potential applications in catalysis, sensors, gas storage, and solar energy conversion. On account of their unique desirable properties, porphyrins have been ideal building blocks for the construction of functional MOPAs, working as prosperous functional porous materials for gas storage and adsorption/desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins are promising components that can be employed in various applications due to their desirable structural and functional properties. Moreover, prophyrins are capable of being incorporated into metal–organic–polymer aerogels, which have both the physicochemical properties of porphyrins and the permanent porosity of MOPAs . Porphyrin-based metal–organic frameworks have been extensively investigated , as a versatile synthetic base for porous metal–organic frameworks due to their potential applications in catalysis, sensors, gas storage, and solar energy conversion. On account of their unique desirable properties, porphyrins have been ideal building blocks for the construction of functional MOPAs, working as prosperous functional porous materials for gas storage and adsorption/desorption.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, microscopic analysis has revealed the presence of differently shaped aggregates, such as rod, and nanotubular structures, depending on the experimental conditions [35,43,46]. Moreover, a detailed study has revealed that porphyrin concentration strongly affects the amount of J-aggregate adsorbed onto glass surfaces, showing a higher number of adsorbed entities at lower porphyrin concentrations [47]. In the past, J-aggregated porphyrin has been exploited for the design of inorganic/organic nanocomposites in combination with gold nanoparticles and spermine [48] or with gold nanorods [36,49].…”
Section: Introductionmentioning
confidence: 99%
“…7,1020 The heights and lengths of the TPPS 4 nanorods range from several to dozens of nanometers in diameter and up to several micrometers in length. 4,10,13,19,20 The size and shapes of the nanorods derived from TPPS 4 are due to a combination of molecular interactions such as Coulombic interactions, π – π interactions, and intermolecular electrostatics. 21 Studies were reported by Schuckman et al of the charge transport properties of a tethered Zn(II) porphyrin thiol complex, tripyridyl porphyrin, in which molecular clusters were inserted within an alkanethiol matrix on Au(111).…”
Section: Introductionmentioning
confidence: 99%
“…Methods of surface fabrication with porphyrin nanorods include surfactant-assisted self-assembly, ionic self-assembly, , mixed porphyrin self-assembly, sonication-assisted self-assembly, and metal coordination-assisted self-assembly. Among the studies reported for porphyrin nanorods, rodlike aggregates derived from meso-tetra­(4-sulfonato­phenyl)­porphyrin (TPPS 4 ) are a well-studied example because it is a biomimetic analogue of photosynthesis systems. , The heights and lengths of the TPPS 4 nanorods range from several to dozens of nanometers in diameter and up to several micrometers in length. ,,,, The size and shapes of the nanorods derived from TPPS 4 are due to a combination of molecular interactions such as Coulombic interactions, π–π interactions, and intermolecular electrostatics . Studies were reported by Schuckman et al of the charge transport properties of a tethered Zn­(II) porphyrin thiol complex, tripyridyl porphyrin, in which molecular clusters were inserted within an alkanethiol matrix on Au(111). , …”
Section: Introductionmentioning
confidence: 99%